رسول اللہ ﷺ کے دندان مبارک شہید ہونےکی روایت : اردو کتب کا اختصاصی مطالعہ: The Narration about the Martyrdom of the Tooth of the Holy Prophet ﷺ: An Explicit Study of Urdu Literature - Khalid Mahmood Khan; Dr. Allah Ditta(Corresponding Author); Dr. Muhammad Ramzan Saeedi (International Research Journal of Arabic and Islamic Studies, 2022)
This article is an attempt to understand the correct insight about the incident of tooth decay from the Seerah of the Holy Prophet. The life of the Holy Prophet is a perfect example for Muslims, and the perfect following of Holy Prophet is mandatory for attaining the pleasure of God and entering the Paradise. Therefore, complete obedience to the Messenger of Allah ﷺ is obligatory for every Muslim. Therefore, a proper understanding of the Prophet's life is essential for every Muslim, because if there is no proper understanding of the Prophet's life, then the Muslims will not be able to act correctly. Unfortunately, many misconceptions about the life of the Holy Prophet ﷺ have become common among Muslims. One of these misunderstandings among the Muslims and especially among the Muslims of Sub-continent, who are the Urdu-speaking nation, is that this misunderstanding has become common that the four blessed teeth of the Messenger of Allah ﷺ were martyred. Even many famous and renowned researchers and writers have also stated that the four blessed teeth of the Prophet ﷺ were martyred. In this article, the incident of tooth decay will be examined and detailed answers will be given to the related questions as well. In this regard, historical and inferential research methods have been used and the results and recommendations have been clarified.